Hubungan Riwayat Kekurangan Energi Kronis (KEK) Ibu Hamil dengan Kejadian Stunting Balita - Marlina Marlina; Putu Rangga Dewi Dasi; Indah Trianingsih; Adinda Juwita Sari (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Cases of pregnant women experiencing SEZ, which increases the risk of low birth weight and stunting, are still found in East Lampung District. Purpose: To determine the relationship between the history of chronic energy deficiency (CED) in pregnant women and the incidence of stunting in children under five. Method: Correlation analytic study with cross-sectional design. The population in this study were all mothers who had toddlers aged 0-59 months in 2023 totaling 1030 recorded in medical records (secondary data) with a research sample of 100 respondents. The independent variable in this study is the history of maternal SEZ when pregnant and the independent variable is stunitng in toddlers aged 0-59 months. The sampling technique used was proportional random sampling technique. Data collection tools in the form of a checklist. Data analysis used univariate with percentage, bivariate with Chi Square. Results: The study showed that toddlers who were stunted were 21% and mothers who had a history of SEZ were 26%. Conclusion: The results of statistical tests can be concluded that there is a highly significant relationship between the history of SEZ in pregnant women and the incidence of stunting in toddlers with a p-value of 0.000 with an OR of 22,080. Suggestion: Researchers suggest conducting more in-depth longitudinal studies to evaluate the effectiveness of long-term nutrition interventions and examining other factors such as socioeconomics, access to health services, and environmental factors that influence SEZ and stunting. The development of new intervention models that are more effective in accordance with local conditions is also needed to address nutrition problems more comprehensively. Keywords: Community Health Center; Health Center; Nutrition Problem. Pendahuluan: Kasus ibu hamil yang mengalami KEK, yang meningkatkan risiko bayi lahir dengan berat rendah dan stunting masih ditemukan di Kabupaten Lampung Timur. Tujuan: Untuk mengetahui hubungan antara riwayat kekurangan energi kronis (KEK) pada ibu hamil dengan kejadian stunting pada balita. Metode: Penelitian analitik korelasi dengan rancangan cross-sectional. Populasi dalam penelitian ini adalah seluruh ibu yang memiliki balita usia 0-59 bulan tahun 2023 berjumlah 1030 yang tercatat dalam rekam medik (data sekunder) dengan sampel penelitian ada 100 responden. Variabel independen dalam penelitian ini riwayat KEK ibu ketika hamil dan variabel independennya stunitng pada balita usia 0-59 bulan . Teknik sampling yang digunakan adalah teknik porposional random sampling. Alat pengumpulan data berupa ceklist. Analisis data yang digunakan univariat dengan persentase, bivariat dengan Chi Square. Hasil: Penelitian terlihat bahwa balita yang mengalami stunting sebanyak 21% dan ibu yang mengalami Riwayat KEK sebanyak 26%. Simpulan: Hasil uji statistik dapat disimpulkan adanya hubungan yang sangat signifikan antara hubungan Riwayat KEK pada ibu hamil dengan kejadian stunting pada balita dengan p-value 0.000 dengan OR 22.080. Saran: Peneliti menyarankan untuk melakukan studi longitudinal yang lebih mendalam untuk mengevaluasi efektivitas intervensi gizi jangka panjang dan meneliti faktor-faktor lain seperti sosioekonomi, akses layanan kesehatan, dan faktor lingkungan yang mempengaruhi KEK dan stunting. Pengembangan model intervensi baru yang lebih efektif sesuai dengan kondisi lokal juga diperlukan untuk menangani masalah gizi secara lebih komprehensif.